2009
DOI: 10.1002/jbm.b.31353
|View full text |Cite
|
Sign up to set email alerts
|

Temperature evaluation during PMMA screw augmentation in osteoporotic bone—An in vitro study about the risk of thermal necrosis in human femoral heads

Abstract: The use of polymethylmethacrylate (PMMA) bone cement to augment hip screws reduces cut-out risk but is associated with an exothermic reaction. This in vitro investigation evaluated the risk of thermal necrosis when augmenting the implant purchase with PMMA. A pilot study analyzed the effects of different PMMA layer thicknesses on temperatures around an implant. The main study used either 3.0 or 6.0 cc PMMA for hip screw augmentation in human femoral heads. The risk of thermal necrosis was estimated according t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
52
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(55 citation statements)
references
References 23 publications
2
52
0
1
Order By: Relevance
“…The same study also showed that the reached temperature is dependent on the amount of injected cement. For the present study, a lower amount of cement was used (mean 3.8 ml) and it is assumed that this amount does not lead to negative impact on both bone and cartilage as previously described [4,43]. Our findings that there were no radiological signs of osteonecrosis at follow-up and that there was no significant change of the joint space support this statement.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The same study also showed that the reached temperature is dependent on the amount of injected cement. For the present study, a lower amount of cement was used (mean 3.8 ml) and it is assumed that this amount does not lead to negative impact on both bone and cartilage as previously described [4,43]. Our findings that there were no radiological signs of osteonecrosis at follow-up and that there was no significant change of the joint space support this statement.…”
Section: Discussionsupporting
confidence: 72%
“…The main concerns about such a device were a potential disturbance of bone metabolism [14,19,37] and the induction of cartilage damage although there are several investigations rebutting this [4,41,43]. The current prospective multicenter trial was conducted to evaluate the long-term clinical outcome as well as the radiological results with the standardized augmentation of the PFNA.…”
mentioning
confidence: 99%
“…This supports the theory that there is no thermal damage to the bone due to the exothermic reaction of the PMMA in a standardised augmentation setting with only a small amount of cement injected. 26,28 The mean cement volume of 4.2 ml used in our study was able to increase stability in biomechanical investigations. 14,20,23,26 However, with this small amount of cement damage to the bone is unlikely.…”
Section: Discussionmentioning
confidence: 72%
“…26,28 The mean cement volume of 4.2 ml used in our study was able to increase stability in biomechanical investigations. 14,20,23,26 However, with this small amount of cement damage to the bone is unlikely. 14 In this context, it has to be mentioned that our follow-up time could be too short for a statement about bone necrosis, as several authors report the time to onset up to 3 years after the fracture.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation